The impacts of distinct light spectra on the growth properties and maternal productivity of rats - Tirascı, N; Simsek, UG (Journal of the Hellenic Veterinary Medical Society, 2025)
The study aimed to determine how the complete visible light spectrum and white light affected the growth characteristics of rat puppies, oxidative stress measures, and mother fertility. For the purposes of the study, a total of 56 female and 28 male breeding rats (Sprague Dawley) were mated, with 8 female and 4 male rats per group. Growth characteristics were followed until the 63rd day. At the end of the research, 4 female and 4 male rats from each group were euthanized under anesthesia. Oxidative stress parameters were determined in their blood samples. The group that received green lighting had the highest puppy yield and weaning rate. The blue lighting group had the highest live weight and live weight gain during the suckling period. The groups that were red and green had the highest pubertal weights. The highest feed consumption was obtained in the green lighting group. Feed utilization and water consumption were found to be similar among the lighting groups. The white lighting group had the highest total antioxidant level (TAS), while the red lighting group had the lowest. The highest total oxidant (TOS) and oxidative stress index (OSI) were found in the red group. These results suggest that rats were affected differently by the light spectrum at varying physiological periods.